Cultural Variation in the Theory of the Firm - Donald W. Katzner (University of Massachusetts, Department of Economics, 2005)
This paper presents a model of the firm that includes the possibility of firm and employee-on-the-job decision making based on alternatives to profit and utility maximization. Such alternatives are relevant and significant when explaining firm activity in cultural environments in which self interest is not considered to be a primary force driving human behavior. Three types of firms are defined and their properties compared: the Western firm, the Japanese firm, and the clan. The third is a combination of the first two. JEL Categories: D21, Z19
Keywords: 330; Culture; firm; decision making